Construction and Preliminary Analysis of Three-dimensional Model of Offshore Wind Power Suction Bucket. (September 2020) - Zhang, Xu; Xiao, Jiandong; Lin, Yifeng
Abstract: As a high-rise structure, offshore wind turbines are subjected to huge horizontal loads. Compared with the traditional tubular foundation for offshore wind power, the large-scale tubular foundation with a load-bearing top has a larger load-bearing capacity due to its unique broad-shallow tubular top load-bearing mode. For reasons of towing stability, construction subsidence, fine leveling and structural strength, a subdivision plate is arranged in the concrete cylinder foundation cylinder. We established solid and structural elements through numerical methods, and took into account the tube-soil contact, so as to finely construct a real three-dimensional complex model of this new type of tube-based foundation and soil, which plays an important role in analyzing its deformation and bearing characteristics, as well as the safety and stability of the foundation structure design and practical application.